Maternal psychosocial well-being in Eritrea: application of participatory methods and tools of investigation and analysis in complex emergency settings - Almedom Astier M.; Tesfamichael Berhe; Yacob Abdu; Debretsion Zaïd; Teklehaimanot Kidane; Beyene Teshome; Kuhn Kira; Alemu Zemui (The World Health Organization, 2003)
Objective: To establish the context in which maternal psychosocial well-being is understood in war-affected settings in Eritrea. Method: Pretested and validated participatory methods and tools of investigation and analysis were employed to allow participants to engage in processes of qualitative data collection, on-site analysis, and interpretation. Findings: Maternal psychosocial well-being in Eritrea is maintained primarily by traditional systems of social support that are mostly outside the domain of statutory primary care. Traditional birth attendants provide a vital link between the two. Formal training and regular supplies of sterile delivery kits appear to be worthwhile options for health policy and practice in the face of the post-conflict challenges of ruined infrastructure and an overstretched and/or ill-mannered workforce in the maternity health service. Conclusion: Methodological advances in health research and the dearth of data on maternal psychosocial well-being in complex emergency settings call for scholars and practitioners to collaborate in creative searches for sound evidence on which to base maternity, mental health and social care policy and practice. Participatory methods facilitate the meaningful engagement of key stakeholders and enhance data quality, reliability and usability.